Mastering the Grammar of Complex Events: Evidence from Mandarin Resultative Verb Compounds. Issue 3 (3rd July 2019) - Hsu, Ning; Rispoli, Matthew; Hadley, Pamela A.
ABSTRACT: The Mandarin resultative verb compound (RVC; e.g., tui dao "push fall" and pa shang "climb ascend") encodes complex events composed of an initiating action and resulting activity or state. This study investigated when Mandarin-speaking children acquired this language-specific device. Specifically, we focused on children's production of RVCs with two infixes, - bu- "not able" and - de- "be able." Because the infixes intervene between the two verbs of RVC (e.g., tui -bu- dao "push -not able- fall" and tui -de- dao "push -be able- fall"), being able to produce RVC infixation indicates that children have a morphological separation between the action and the result verbs. Two studies were conducted. Study 1 is a corpus analysis. We examined the use of plain RVCs versus RVCs with infixes in parent input and children's spontaneous speech using a cross-sectional corpus and a longitudinal corpus. RVCs with infixes were found to be very rare in both parent input and child production. Study 2 is an experimental elicitation task targeting RVC infixation. Children between 3;0 and 5;0 performed exceptionally well, producing target responses when primed with structurally related probes in discourse-appropriate contexts. There was no difference in children's performance related to age or the type of infix (i.e., - bu - vs - de -). Children's early competence with RVC infixation, which is infrequent in input, runs counter to the usage-based approach that emphasizes item-based learning. Rather, by age three, Mandarin-speaking children have developed a representation of the RVC as two distinct morphemes for encoding complex event structure. This representation facilitates acquisition of the infixes with very little input data.